2004
DOI: 10.1159/000079960
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Anatomical Asymmetries of Transverse Sinuses: An MR Venographic Study

Abstract: Time-of-flight (TOF) magnetic resonance venography (MRV) is often used to examine the intracranial dural sinuses, particularly in the evaluation of dural sinus thrombosis. The goal of the study was to evaluate the use of TOF MRV in assessing the normal anatomy of dural sinuses and their variations as sources of potential pitfalls in the diagnosis of venous sinus thrombosis. Cerebral TOF MRV obtained in 105 persons with normal MR studies were reviewed to determine the presence, aplasia and hypoplasia of the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
70
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(91 citation statements)
references
References 10 publications
14
70
0
4
Order By: Relevance
“…Previous examinations of venous asymmetry have shown the right transverse sinus to be larger in 59% of cases (Ayanzen et al, 2000), and the left transverse sinus to be aplastic or hypoplastic in 59% of cases (Alper et al, 2004)this is congruent with our finding of 54.6% of skulls having a correlation between right-sided SSVS and a larger JF on the right. Significant differences were also observed in the frequency of right SSVS-JF skulls, with Otago skulls having more of this combination than Coimbra.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous examinations of venous asymmetry have shown the right transverse sinus to be larger in 59% of cases (Ayanzen et al, 2000), and the left transverse sinus to be aplastic or hypoplastic in 59% of cases (Alper et al, 2004)this is congruent with our finding of 54.6% of skulls having a correlation between right-sided SSVS and a larger JF on the right. Significant differences were also observed in the frequency of right SSVS-JF skulls, with Otago skulls having more of this combination than Coimbra.…”
Section: Discussionsupporting
confidence: 92%
“…The majority of forebrain superficial veins drain into the SSVS (Beards et al, 1998;Brockman et al, 2012); it is located in the sagittal plane at the superior border of the falx cerebri running anterior to posterior from the crista galli of ethmoid bone to termination in the transverse sinus ( Figure 3). The SSVS is described as terminating in (draining into) the right transverse sinus in the majority of individuals (Browning, 1953;Ayanzen et al, 2000;Alper et al, 2004); the transverse sinus then passes anterolaterally to become the sigmoid sinus, then turning medially and passing anteriorly to enter the JF and become the internal jugular vein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alper et al, [12] described flow gaps in 24% of normal population. Our study revealed flow gaps [ Table 1] more at the sigmoid transverse junctions or in the lateral most aspect of the transverse sinus and to a lesser extent in the sigmoid sinus.…”
Section: Discussionmentioning
confidence: 99%
“…Alper et al, [12] described about transverse sinus abnormalities -20% aplasia and 39% hypoplasia of the left sinus, 6% hypoplasia and 4% aplasia of the right sinus and 31% symmetric sinuses. Our results also show most of the hypoplastic and aplastic transverse sinuses were on the left side only.…”
Section: Discussionmentioning
confidence: 99%